Life and Debt: The Experiences of Black Women use of Student Loan Programs for Graduate Education Advancement - Natasha Webster (Adult Education Research Conference, 2023)
This qualitative study examined the experiences of adult Black women doctoral graduates and the use of student loans to advance and gain financial prosperity.
Keywords: student debt; Black women graduates